Experience with the potassium binder patiromer in hyperkalaemia management in heart failure patients in real life - Alberto Esteban‐Fernández; Carolina Ortiz Cortés; Silvia López‐Fernández; Alejandro Recio Mayoral; Francisco Javier Camacho Jurado; Inés Gómez Otero; María Molina; Luis Almenar Bonet; Raquel López‐Vilella (ESC Heart Failure, 2022)
Abstract Aims Hyperkalaemia (HK) is common in heart failure (HF) patients, related to renal dysfunction and medical treatment. It limits medical therapy optimization, which impacts prognosis. New potassium (K) binders help control HK, allowing better medical management of HF. Methods and results A retrospective multicentre register included all outpatients with HF and HK (K ≥ 5.1 mEq/L) treated with patiromer according to current recommendations. We evaluated analytic and clinical parameters before starting the treatment and at 7, 30 and 90 days, as well as adverse events related to patiromer and treatment optimization. We included 74 patients (71.6% male) with a mean age of 70.8 years (SD 9.2). Sixty‐seven patients (90.5%) presented HK in the previous year. Forty patients (54.1%) underwent down‐titration of a renin–angiotensin–aldosterone inhibitor (RAASi) or a mineralocorticoid receptor antagonist (MRA), and 27 (36.5%) stopped any of them due to HK. Initial K was 5.5 mEq/L (SD 0.6), with a significantly reduction at 7 days (4.9 mEq/L (SD 0.8); P < 0.001), maintained at 90 days (4.9 mEq/L (SD 0.8); P < 0.001). There were no other electrolyte disturbances, with a slight improvement in renal function [glomerular filtration rate 39.6 mL/min (SD 20.4) to 42.7 mL/min (SD 23.2); P = 0.005]. Adverse events were reported in 33.9% of patients, the most common being hypomagnesaemia (16.3%), gastrointestinal disturbances (14.9%) and HK (2.8%). Withdrawal of patiromer was uncommon (12.2%) due to gastrointestinal disturbances in 66.7% of cases. Nine patients (12.2%) started on a RAASi, and 15 patients (20.3%) on an MRA during the follow‐up. Forty‐five patients (60.8%) increased the dose of RAASi or MRA, increasing to target doses in 5.4 and 10.8% of patients, respectively. At 90 days, NTproBNP values were reduced from 2509.5 pg/mL [IQR 1311–4,249] to 1396.0 pg/mL [IQR 804–4263]; P = 0.003, but the reduction was only observed in those who optimized HF medical treatment [NTproBNP from 1950.5 pg/mL (IQR 1208–3403) to 1349.0 pg/mL (IQR 804–2609); P < 0.01]. NYHA functional class only improved in 7.5% of patients, corresponding with those who optimized HF medical treatment. Compared with the previous 3 months before patiromer treatment, the rate of hospitalization was reduced from 28.4 to 10.9% (P < 0.01), and the emergency room visits from 18.9 to 5.4% (P < 0.01). Conclusions In a real‐life cohort of patients with HF, patiromer reduced and maintained K levels during 3 months of follow‐up. The most common adverse events were hypomagnesaemia and gastrointestinal disturbances. Patiromer helps optimize medical treatment, increasing the percentage of patients treated with RAASi and MRA at target doses. At the end of follow‐up, natriuretic peptides values and hospital visits were reduced, suggesting the benefit of optimizing HF medical treatment.